2015
DOI: 10.1021/acsbiomaterials.5b00312
|View full text |Cite|
|
Sign up to set email alerts
|

Trehalose-Based Block Copolycations Promote Polyplex Stabilization for Lyophilization and in Vivo pDNA Delivery

Abstract: The development and thorough characterization of nonviral delivery agents for nucleic acid and genome editing therapies are of high interest to the field of nanomedicine. Indeed, this vehicle class offers the ability to tune chemical architecture/biological activity and readily package nucleic acids of various sizes and morphologies for a variety of applications. Herein, we present the synthesis and characterization of a class of trehalose-based block copolycations designed to stabilize polyplex formulations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 61 publications
0
60
0
Order By: Relevance
“…22, 28 Others have shown that polymers with trehalose side chains can inhibit amyloid formation and form stable nanoparticles for nucleic acid delivery. 2931 We hypothesized that trehalose glycopolymers would also stabilize proteins in vivo similar to PEG. In the study described here, for the first time we demonstrate that the trehalose glycopolymer can maintain the plasma protein concentration within the therapeutic window over an extended period of time and also stabilize a protein therapeutic at elevated temperature and under mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…22, 28 Others have shown that polymers with trehalose side chains can inhibit amyloid formation and form stable nanoparticles for nucleic acid delivery. 2931 We hypothesized that trehalose glycopolymers would also stabilize proteins in vivo similar to PEG. In the study described here, for the first time we demonstrate that the trehalose glycopolymer can maintain the plasma protein concentration within the therapeutic window over an extended period of time and also stabilize a protein therapeutic at elevated temperature and under mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it was proposed that the clam shell conformation, bending of the anomeric position of trehalose disaccharide leading to the two glucose ring coming into close proximity, taken up the trehalose may be more important than the regiochemistry of the vinyl benzyl ether. Interestingly, a trehalose block copolycation consisting of 6-methacrylamido-6-deoxy trehalose-co-N(2-aminoethyl) methacrylamide (pMAT-b-AEMA) was an effective polyplex with short interfering RNA (siRNA) (244) for gene knockdown in cultured glioblastoma (U87), and pT2/CaL plasmid DNA (pDNA) (245) for gene delivery in U87 and human liver carcinoma (HepG2) cell lines. In both cases high stability and minimum toxicity were reported for the polyplexes.…”
Section: Glycopolymer Conjugatesmentioning
confidence: 99%
“…Since this, covalent incorporation of trehalose in macromolecules has received continuous interest with more than fifty known publications available (Scopus database). Polymers containing trehalose were obtained using various polymerization and post-polymerization techniques and were studied as e.g., excipients for protein stabilization under deactivating conditions [14][15][16][17], nonviral nucleic acid carriers [18][19][20], thermogelling hydrogel matrices for 3D cancer cell culture [21], and magnetic nanoparticles for selective interactions with mycobacteria [22]. In our recent studies, we presented the utilization of trehalose derivatives in hydrogels synthesis as hydrolytically-labile crosslinkers [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%